2012
DOI: 10.1016/j.chroma.2012.08.095
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic chips with reversed-phase monoliths for solid phase extraction and on-chip labeling

Abstract: The integration of sample preparation methods into microfluidic devices provides automation necessary for achieving complete micro total analysis systems. We have developed a technique that combines on-chip sample enrichment with fluorescence labeling and purification. Polymer monoliths made from butyl methacrylate were fabricated in cyclic olefin copolymer microdevices and used for solid phase extraction. We studied the retention of fluorophores, amino acids and proteins on these columns. The retained samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 57 publications
3
57
0
Order By: Relevance
“…To avoid potential loss of hydrophobic analytes to polymer gasket materials (a process for which we find evidence especially from low-concentration analyte solutions), an all-glass microscopy flow cell was constructed from an optically flat float-glass top plate and coverslip, assembled by cold welding where the clean flat-glass surfaces are likely held together by strong hydrogen bonding interactions. A 0.5 mm wide by 0.2 mm deep flow channel was machined into a 25 mm diameter float-glass top 4 OH, which was then heated to 70°C for 10 min. The plate and coverslip were then rinsed with the deionized water, held in contact with an aluminum screw clamp, and heated to 180°C for at least 3 h. After a gradual lowering to room temperature (4−6 h), the coverslip and top plate were bonded, producing a sealed channel between the inlet and well.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…To avoid potential loss of hydrophobic analytes to polymer gasket materials (a process for which we find evidence especially from low-concentration analyte solutions), an all-glass microscopy flow cell was constructed from an optically flat float-glass top plate and coverslip, assembled by cold welding where the clean flat-glass surfaces are likely held together by strong hydrogen bonding interactions. A 0.5 mm wide by 0.2 mm deep flow channel was machined into a 25 mm diameter float-glass top 4 OH, which was then heated to 70°C for 10 min. The plate and coverslip were then rinsed with the deionized water, held in contact with an aluminum screw clamp, and heated to 180°C for at least 3 h. After a gradual lowering to room temperature (4−6 h), the coverslip and top plate were bonded, producing a sealed channel between the inlet and well.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…38,[40][41][42][43][44][45][46][47][48] Recently, we presented the first application for PPMs on DMF 36 using PPM discs with C12 moieties as a reverse phase for SPE. With the goal of expanding this technique to include SCX extractions, Fig.…”
Section: Ppm Formation and Characterisationmentioning
confidence: 99%
“…Importantly, there is a need for integrated microfluidic systems with monoliths for sample preparation. Recently, Nge et al [39] reported a monolith prepared from butyl methacrylate for SPE and on-chip labeling. However, pretreatment of the monolith by rinsing with 30% acetonitrile was necessary to obtain the best retention.…”
Section: Introductionmentioning
confidence: 99%